Territorial marginality: Causes, methods and policies. Introduction to the special issue - Bruna Vendemmia; Agim Kërçuku; Giovanni Vecchio (REGION, 2023)
What are the different factors that make a territory marginal? Are contextual features related to spatial, socioeconomic, institutional, or cultural elements differently influencing marginality in different countries? These are the questions at the origin of this Special Issue. Marginal areas are traditionally defined as those far from the main urban centres, based on a core-periphery model (Cullen & Pretes, 2000; Gatzweiler & Baumüller, 2014; Herrschel, 2012; Ferrau & Lopes, 2004; Bock, 2016). From this perspective, marginality is an intrinsic spatial condition rather than a transient feature. However, the geographic distance from the poles is only one among the many conditions that can help to define marginality, which could be better defined as a process deeply influenced by socioeconomic changes (Máliková, Farrell, McDonagh, 2016). Marginal regions can be peripheral in geographical location but advanced regarding their socioeconomic situation. On the other hand, not every marginal Region is necessarily peripheral: on the contrary, several studies suggest an interpretation of marginality as a lack of socioeconomic and political connection (Leimgruber, 2004; Pelc, 2006; Bock, 2016). Moreover, in European countries such as Germany, France and Italy, the concept of marginality has often been associated with rural or mountainous areas. Still, different contributions to this Special Issue show that marginal territories may have very diverse geographical and orographic conditions. In addition, the scale at which a region can be defined as marginal and the administrative borders may also significantly influence the definition of marginality itself. The lack of a broad, shared definition of marginality affects the identification of marginal territories and the possibility of developing adequate territorial policies to rebalance their marginal condition. Europe shows different attempts at defining marginal territories before proposing devoted policies. For example, Italy refers to the concept of "inner areas" (Materiali Uval, 2014), while the Espon (2017) project PROFECY refers to "inner peripheries". The different names given to marginal territories and the different definitions of marginality require exploring the meaning of considering the other features that may make a territory marginal. As a result, marginality should move from the core-periphery model that considers accessibility to services and goods and distance from central places, considering how a combination of physical, social, economic, institutional and cultural aspects defines marginal territories.
Keywords: 330